Assessing and explaining the female condom uptake in Chikomba District. - Matenhese, Lucy (Midlands State University, 2017)
HIV /AIDS has been a major problem in Zimbabwe and mostly affecting women such that of the infected people in Sub Saharan Africa women constituted 60% . This growing evidence led to the introduction of the female condom in 1997. In Chikomba district despite the introduction of the female condom its uptake is significantly low. The theory of planned behaviour and the Health belief model guided through understanding the findings of the research. The study was largely qualitative and with the use of interview and Focus group discussions as data collection methods. This was an analytical survey in which the sample size was 94 participants .Data gathered was analysed using thematic techniques. The study revealed that the female uptake in Chikomba district was significantly low and this was attributed to a number of factors such as lack of knowledge, socio cultural barriers, lack of male involvement, mechanical factors such as the shape of the female condom, myths and misconception surrounding, unavailability of the device and high cost .As means of enhancing the uptake of the female condom the government of Zimbabwe through the Ministry of Health and Child Welfare was recommended to channel funds to the promotion of the female condom as a long term program .Providers were also recommended to lower the cost of the device, educate people using models, involve males, and also target traditional and religious leaders